THE USE OF DESCRIBING PICTURE STRATEGY TO IMPROVE SECONDARY STUDENTS’ SPEAKING SKILL - Zakiyah Farhanah Pratiwi; Mutiara Ayu (fsip.teknokrat.ac.id, 2020)
Describing picture strategy is one of the techniques that can be used to improve students' speaking skills. Speaking skill is one of the subjects that difficult to be mastered by young learners. This study was conducted in SMA Al Azhar 3 Bandar Lampung at first-grade students. With qualitative data, the result showed that describing a picture strategy can improve students' speaking skills. This finding is in line with the previous research finding that describing pictures can help students to improve students’ speaking skills. Nevertheless, there are some problems gained in using describing picture strategy. Many students could not apply grammar correctly when they speak by using the strategy. The students are difficult to understand English when their friends speak English using describing the picture.